2003
DOI: 10.1051/gse:2003031
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships of Red Jungle Fowl and chicken breeds

Abstract: Published results were reassessed and original data are provided regarding the origin and relatedness of four postulated chicken breed lineages, egg-type, game, meat-type and Bantam, to each other and to the basic ancestral species of jungle fowls, Gallus gallus. A system approach was employed concerning the planning of the experiments. One element of the system approach is the choice of the breeds to be compared with G. gallus. These breeds were supposed to represent major evolutionary branches of chickens. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 22 publications
(35 reference statements)
2
27
1
Order By: Relevance
“…Currently, however, these breeds are genetically closer to each other than to the wild roosters. A study on the evolution of birds of the genus Gallus and the origin of the successive breeds has suggested that the different types of birds have not appeared simultaneously (Moiseyeva et al, 2003). Furthermore, it has been also considered that egg-type breeds, or Mediterranean breeds, are possibly the oldest, and the fighting breeds have evolved either directly from the wild ancestors or from the egg-type breeds shortly after (Moiseyeva et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, however, these breeds are genetically closer to each other than to the wild roosters. A study on the evolution of birds of the genus Gallus and the origin of the successive breeds has suggested that the different types of birds have not appeared simultaneously (Moiseyeva et al, 2003). Furthermore, it has been also considered that egg-type breeds, or Mediterranean breeds, are possibly the oldest, and the fighting breeds have evolved either directly from the wild ancestors or from the egg-type breeds shortly after (Moiseyeva et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A study on the evolution of birds of the genus Gallus and the origin of the successive breeds has suggested that the different types of birds have not appeared simultaneously (Moiseyeva et al, 2003). Furthermore, it has been also considered that egg-type breeds, or Mediterranean breeds, are possibly the oldest, and the fighting breeds have evolved either directly from the wild ancestors or from the egg-type breeds shortly after (Moiseyeva et al, 2003). Komiyama et al (2003) has identified the origin of the Japanese breed Shamo and its precedence over three variations of singing roosters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same author suggested that most or all of the continental subspecies of RJFs were involved in the genesis of the modern domestic chicken. In addition, it was reported that the domestication has continued through an extensive breeding programs, which has resulted in many breeds of chickens representing four distinct lineages: egg-type, game, meat-type, and bantam (Moiseyeva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Wheel-made terracotta bird askoi, resembling a rooster with a short tail and crest of feathers, were created and deposited in tombs at the Kerameikos beginning around 750 BC. 51 Cockerels are first depicted in Corinthian and Athenian 47 Scientific and biological studies based on the DNA of modern and ancient chickens, trace the ancestry of all chickens to Red Jungle Fowl, from which six diverse domesticated breeds stem (Fumihito 1994, 12505;Kanginakudru et al 2008;Moiseyeva 2003). 48 Serjeantson 2009, 269.…”
mentioning
confidence: 99%